Examining the Influence of Forestry Value Added Dimensions on Climate Change in Thailand - Suratman, Maman; Hitam, Mizan (International Journal of Energy Economics and Policy, 2021)
To get the meaningful results against the increasing challenges of the nature and climate, more focus is required towards sustainability in multiple dimensions. This study examines the six dimensions of forestry on four measures of climate change. The time duration of this study has considered the five decades; 1970-2018 on annual basis. Overall results are presented under descriptive results (Table 2 and Table 3), whereas findings for the individual coefficients are presented under Table (4-7). It is observed that There is a negative impact of agriculture, forestry, and fishing or FA on electric power consumption abbreviated as CH1, whereas positive and significant impact from FD, FE and FF is observed (Table 4). On the other hand, for CH2 or energy usage, key determinants are FA, FD-FF under full sample period. For CH3 or Nitrous Oxide emission, there is highly significant and negative impact from FA, while FD and FF are also positively influencing the Nitrous Oxide emission during 1970-2018 on annual basis. For Methane emissions, positive determination is experienced from FD and FF. The findings under present study would provide good understand for the relationship between forestry factors and climate change dimensions in Thailand. In addition, literature contribution is also observed with the help of present study and in the regional context of Thailand too. As per the implication present study can be utilized for examining the relationship between forestry factors and climate change dynamics. However, some limitations are associated with this research like, examining the two directional association between forest and climate change, cross sectional regional comparisons, and implication of both short and long term relationship between the variables of the study. Future studies may reasonably address these limitations as it can provide some more literature contribution in the targeted fields. Keywords: Forestry factors, Climate Change, energy. JEL Classifications: Q23, Q54, P18 DOI: https://doi.org/10.32479/ijeep.10934